Utilizing AI (Artificial Intelligence) to Have Positive Impacts on Students in Learning English - Telaumbanua, Yasminar Amaerita; Hulu, Nesti Arni; Zai, Ayu Kartika; Hulu, Delan Septiani; Ndruru, Ednis Sartika (Universitas Nusantara PGRI Kediri, 2024)
This research explored the use of Artificial Intelligence (AI) to positively impact on students in learning English. However, the study also recognized the potential negative impacts of AI, such as over-reliance on technology, reduced language expression and grammar proficiency. The purpose of this phenomenological qualitative research was to investigate how AI can be utilized to positively influence students in the context of English language learning. The research method involved collecting and analyzing first-hand experiences from students to understand the nuances of AI integration in English education. In this study, the researchers took second semester students of the English Education Study Program, University of Nias as participants. The research was conducted at the University of Nias. How to use AI to have a positive impact on students in learning English is by filtering the answers generated from AI.